Characteristics and prognostic factors of chronic kidney disease patients with Pneumocystis jirovecii pneumonia - Liu Xiao-hua; Wu Jing-jing; Zeng Ming; Ge Yi-fei; Zhang Bo; Wu Bu-yun; Mao Hui-juan (Linchuang shenzangbing zazhi)
ObjectiveTo explore the clinical and prognostic characteristics of chronic kidney disease （CKD） patients with Pneumocystis jirovecii pneumonia （PJP）， thus facilitating the diagnosis and treatment of Pneumocystis jirovecii infections.MethodsWe retrospectively analyzed the clinical date of 22 CKD patients with PJP who were hospitalized in the First Affiliated Hospital with Nanjing Medical University and diagnosed by metagenomic next-generation sequencing （mNGS） from October 1， 2019 to October 31， 2023. Based on the prognosis， CKD patients with PJP were divided into the cured group （n=14） and death group （n=8）. The clinical characteristics， laboratory examination indicators， and disease treatment situations of the two groups of patients were compared.ResultsA total of 22 CKD patients were diagnosed with PJP， including 6 males （27.3%） and 16 females （72.7%）. The mean age was （57.1 ± 16.3） years. The primary underlying diseases were membranous nephropathy， immunoglobulin A nephropathy （IgAN）， lupus nephritis，antineutrophil cytoplasmic antibody （ANCA）-associated glomerulonephritis. The median time of PJP was 3 （2， 108） months after the diagnosis of nephropathy. Totally 16 （72.7%） patients developed type Ⅰ respiratory failure. All patients had a history of glucocorticoids or immunosuppressants use 3 months prior to PJP. CT findings included mixed ground-glass opacities type and nodular type （81.8%）. Lactate dehydrogenase （LDH） was elevated in all patients. The 1，3-β-glucan test was positive in 18 patients （81.8%）. Lymphocyte count was low in 16 patients （72.7%）. The cluster of differentiation 4 receptors （CD4） cell count averaged at 292.3 cells/μL， and 60.0% of the patients had CD4 cell count<200 cells/μL. The mean serum creatinine on admission was （232.0 ± 216.6）μmol/L， among which 15 patients （68.2%） developed acute kidney injury and 12 patients （54.5%） required dialysis. All patients received anti-PJP therapy and 16 patients （72.7%） adjusted their medication based on mNGS results. The mean dose of compound sulfamethoxazole was （11.0 ± 5.8）mg·kg-1·d-1 （base on trimethoprim）. Totally 10 patients （45.5%） required mechanical ventilation. Compared with the cured group， the death group had higher oral glucocorticoid dose ［（28.6 ± 12.2）mg vs （18.1 ± 8.8）mg，P=0.039］， more patients required dialysis （7 cases vs 5 cases， P=0.031）， and more patients required mechanical ventilation （7 cases vs 3 cases， P=0.006）.ConclusionClinical symptoms， radiological findings， and laboratory testing should be combined to identify PJP in patients with CKD. The mNGS method is useful for etiological diagnosis of PJP and so facilitate the treatment of PJP. Long-term high-dose oral glucocorticoids， dialysis and mechanical ventilation may be risk factors for poor prognosis in PJP patients.